2018
DOI: 10.2337/dc17-1960
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Accuracy of 18 Marketed Blood Glucose Monitors

Abstract: Cleared BGMs do not always meet the level of analytical accuracy currently required for regulatory clearance. This information could assist patients, professionals, and payers in choosing products and regulators in evaluating postclearance performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
91
1
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(99 citation statements)
references
References 11 publications
(10 reference statements)
1
91
1
5
Order By: Relevance
“…These findings are different from previous recent studies that showed similar measurements for the two methods [10,11,14,22]. Nonetheless, searching the available literature for a comparison with the present results was difficult because most studies on the accuracy of the point-ofcare devices compared capillary (finger stick) glucose measurements with the glucose measures, and were performed in inpatient settings [23]. The present results may be affected by the fact that glucose meters are calibrated to account for differences between capillary blood and venous blood.…”
Section: Discussioncontrasting
confidence: 99%
“…These findings are different from previous recent studies that showed similar measurements for the two methods [10,11,14,22]. Nonetheless, searching the available literature for a comparison with the present results was difficult because most studies on the accuracy of the point-ofcare devices compared capillary (finger stick) glucose measurements with the glucose measures, and were performed in inpatient settings [23]. The present results may be affected by the fact that glucose meters are calibrated to account for differences between capillary blood and venous blood.…”
Section: Discussioncontrasting
confidence: 99%
“…International Organization for Standardization (ISO) and US Food and Drug Administration (FDA) standards require accuracy within 20% of the actual value in 95% of samples with glucose levels ≥75 mg/dL and ±15 mg/dL for glucose levels <75 mg/dL [12]. A recent analysis by the Diabetes Technology Society Blood Glucose Monitor System (BGMS) Surveillance Program revealed that only 6 of 18 commercially available SMBG meters met those standards [15]. In contrast, continuous glucose monitoring (CGM) devices take interstitial glucose readings every 5 minutes and provide a trend analysis.…”
Section: Challenges Of Accurately Measuring Glucose Levelsmentioning
confidence: 99%
“…Moreover, SMBG may not be feasible (or desirable) at work or school, and it is susceptible to user error due to poor testing technique, inadequate blood sample, presence of contaminating substances on fingers, and other factors (32), all of which can lead to primarily falsely high, but also low, readings. Additionally, postmarketing data on the accuracy and consistency of commercially available SMBG systems demonstrated that many did not meet recommended standards (33).…”
Section: Smbgmentioning
confidence: 99%